EFEKTIVITAS PENERAPAN SILABUS YANG BERORIENTASI PADA PESERTA DIDIK DALAM PEMBELAJARAN GITAR DI SANGGAR MUSIK AMABILE - Novenayani, Made Tri; Sumerjana, Ketut; Wiyati, Wahyu Sri (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
Sanggar Musik Amabile is one example of a course in Bali that conducts guitar instrument learning with a learning plan in the form of a syllabus. The syllabus is prepared based on the ABRSM curriculum which is adjusted to the abilities, needs and interests of students to achieve effective learning with maximum results. To find out the effectiveness of the application of the syllabus, a qualitative research was conducted by collecting data through teaching assistance in the form of observation activities and complemented by interview activities. From this research, it was concluded that despite experiencing several obstacles such as: (1) Lack of discipline of students in independent practice, (2) The desire of students to learn songs that are not in accordance with the grade, (3) Lack of concentration of students during learning, (4) The existence of students' willingness that cannot be forced, the application of a learner-oriented syllabus in guitar learning at Amabile Music Studio has been effective because there is conformity between learning planning and its application in the classroom and most of the learning objectives have been achieved.